Putra Transport Sdn Bhd / Mohd Syukri Mahmud ... [et al.] - Mahmud, Mohd Syukri; Shiyamuddin, Salahuddin; Pazikadin, Anwar; Ibrahim, Abd Rahman (Faculty of Mechanical Engineering, 2005)
Putra Transport sdn bhd is intended to be the major transportation service provider in Klang Valley. As a start, our company will give an air conditioning bus service to the community of Klang, Shah Alam and Putrajaya. Putra Transport sdn bhd is a private company owned and operated by Mohd Syukri Bin Mahmud, Salahuddin bin Shiyamuddin, Anwar Bin Pazikadin and Abd. Rahman Bin Ibrahim